THE EFFECT OF STUNTING ON EARLY CHILDHOOD COGNITIVE ABILITIES - Sitti Zaifan; Sri Juani Purwaningsih; Wella Martha Wulan; Reni Rulita; Hera Gustina (International Conferences on Early Childhood Education Proceedings, 2023)
Stunting (short) is one of the problems in growth. Growth disorders can affect children's cognitive development. This study aims to determine whether there are differences in the cognitive abilities of children who are stunted and children who are not stunted in the Bukit Raya sub-district, Pekan Baru city, Riau province. This research is a quantitative research conducted through a survey method. The survey was conducted by detecting the child's stunting condition and assessing the child's cognitive abilities. The results of the research were concluded from a comparison of the cognitive abilities of the group of children who were stunted with children who were not stunted, through non- parameric statistical tests by using your t-test . Sign (+) n1=12, meanwhile sign (-) n2=4. The results of this study indicate that stunting affects early childhood cognitive abilities and it is hoped that with this research educators and parents can pay attention to and meet children's nutritional needs and measure children's growth and development every month so as to optimize children's cognitive development.